2013
DOI: 10.5194/tc-7-631-2013
|View full text |Cite
|
Sign up to set email alerts
|

The influence of climate and hydrological variables on opposite anomaly in active-layer thickness between Eurasian and North American watersheds

Abstract: Abstract. This study not only examined the spatiotemporal variations of active-layer thickness (ALT) in permafrost regions during 1948-2006 over the terrestrial Arctic regions experiencing climate changes, but also identified the associated drivers based on observational data and a simulation conducted by a land surface model (CHANGE). The focus on the ALT extends previous studies that have emphasized ground temperatures in permafrost regions. The Ob, Yenisey, Lena, Yukon, and Mackenzie watersheds are foci of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 57 publications
4
55
0
Order By: Relevance
“…4b), averaged across all sites. In a previous study, CHANGE revealed a cooling bias of −2.1 °C for T SOIL at depths of 0.8-1.2 m (Park et al 2013a). The improved simulation of T SOIL in this study may be partially attributable to the extension of soil depth to 50.5 m.…”
Section: Permafrost Temperature and Active Layer Thicknessmentioning
confidence: 38%
See 3 more Smart Citations
“…4b), averaged across all sites. In a previous study, CHANGE revealed a cooling bias of −2.1 °C for T SOIL at depths of 0.8-1.2 m (Park et al 2013a). The improved simulation of T SOIL in this study may be partially attributable to the extension of soil depth to 50.5 m.…”
Section: Permafrost Temperature and Active Layer Thicknessmentioning
confidence: 38%
“…However, there was better agreement between simulated and observed patterns in western North America, where there are more stations than in the east, and where a decrease in SND has already been identified (Schindler and Donahue 2006). The decrease of snow cover in this region resulted in soil drought and therefore shallower ALTs (Park et al 2013a). Figure 2 compares interannual anomalies in observed and simulated winter SNDs on the pan-Arctic scale.…”
Section: Snow Cover Characteristicsmentioning
confidence: 83%
See 2 more Smart Citations
“…Due to global climate warming, significant efforts have been devoted to permafrost research, such as permafrost variations on the hemispheric-scale permafrost temperature changes (Wu and Zhang, 2008;Guglielmin and Cannone, 2012;Streletskiy et al, 2014;Wu et al, 2015), permafrost degradation (Jorgenson et al, 2006;Ravanel et al, 2010;Sannel and Kuhry, 2011;Streletskiy et al, 2015a;Park et al, 2016), hydrological processes in permafrost regions Wang et al, 2009;Park et al, 2013;Streletskiy et al, 2015b;Ford and Frauenfeld, 2016), feedbacks to climate change (Schuur et al, 2008;Park et al, 2015;Abbott et al, 2016), and other aspects. The increasing thickness of the active layer has been indicated by many observations in permafrost regions at high latitudes and altitudes (Brown et al, 2000;Frauenfeld et al, 2004;Zhang et al, 2005;Fyodorov-Davydov et al, 2008;Wu et al, 2010;Zhao et al, 2010;Callaghan et al, 2011;Liu et al, 2014a, b;Stocker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%